English As A Foreign Language (Efl) Students’ Perception Of Blended Learning At Iain Palangkaraya - Desy Rachmiati; Joni Bungai; Misrita Misrita (Innovative: Journal Of Social Science Research, 2023)
This research aimed to explore the perception of English as a Foreign Language (EFL) students of blended learning at IAIN Palangka Raya. The survey method was used in this research. The participants of the research were 51 students in the fifth semester at English Education Department of IAIN Palangka Raya. Questionnaire was carried out to get the data about the EFL students’ perception of blended learning. The result of the research indicated that EFL students in the fifth semester at IAIN Palangka Raya got positive perception of blended learning. Most students perceived positive perceptions of belief and motivation and also effectiveness and benefit of blended learning.